2018
DOI: 10.1002/pat.4516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene quantum dots on photoluminescence property of polyvinyl butyral nanocomposite

Abstract: Design and development of new photoluminescence system are much in demand for various engineering and technological applications. The present investigation focused on the influence of graphene quantum dots (GQDs) dispersion in the polyvinyl butyral (PVB) matrix. The structural and chemical interaction of GQD‐dispersed PVB composites was confirmed by X‐ray diffraction (XRD), Fourier transform infrared (FTIR), micro‐Raman spectroscopy, ultraviolet and visible (UV‐Vis), and photoluminescence (PL) techniques. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In addition, it can be said that the quantum dots are clamped in the PVB network. 20 Figure 3e-h shows the morphological changes of nanocomposite films after different UV degradation times at a certain BNQDs loading concentration. Before UV degradation, polymer and nanocomposite film materials showed a smoother and layered cross-sectional area, while characteristic surface cracks appeared after different UV degradation times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be said that the quantum dots are clamped in the PVB network. 20 Figure 3e-h shows the morphological changes of nanocomposite films after different UV degradation times at a certain BNQDs loading concentration. Before UV degradation, polymer and nanocomposite film materials showed a smoother and layered cross-sectional area, while characteristic surface cracks appeared after different UV degradation times.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in bandgap as the graphene quantum dot loading rate increased showed that the obtained composites were promising for PL applications. 20 One of the economical and practical aspects of obtaining a high-performance UV protection material is to add UV protection fillers into the polymer matrix. 21 With this motivation, in this study, BNQDs were added into the polymer at different ratios to benefit from the UV protective and photoluminescence properties of quantum dots, as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows Raman spectra of 1, 2 and 3 layers of the (a) B1 (b) B2, (c) B3 and (d) V paints. The Raman spectra of all samples show three distinct Raman peaks for the D band (disordered graphitic site sp3) at around 1384 cm −1 , G band (graphitic site sp2) at around 1518 cm −1 , and 2D band at 2680 cm −1 , which indicate the number of stacked graphitic layers respectively [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, because of its simple synthesis, high conductivity, and great water stability, had a potential material for sensing applications. On the other hand, PVB has excellent adhesion characteristics for electrochemical system 15,23–25 . PVB has limited applicability in the electrical and electrochemical industries due to its low‐electrical conductivity 24,26 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PVB has excellent adhesion characteristics for electrochemical system. 15,[23][24][25] PVB has limited applicability in the electrical and electrochemical industries due to its low-electrical conductivity. 24,26 But lower conductivity of PVB polymer can be optimized by blending with conducting polymer or organic/inorganic fillers and thus can be used for electrochemical system.…”
Section: Introductionmentioning
confidence: 99%